Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/gene.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

IL-7Rα confers susceptibility to experimental autoimmune encephalomyelitis

Abstract: Multiple sclerosis (MS) is a neurological disorder that causes paralysis in young adults and affects women more frequently than men. The etiology of MS is not known, but it is generally viewed as an autoimmune disease of the central nervous system (CNS), influenced by genetic and environmental factors. Recent studies have identified interleukin 7 receptor alpha (IL-7Rα) as a risk factor for multiple sclerosis. But the role of IL-7Rα in experimental autoimmune encephalomyelitis (EAE) model of MS is not known. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Represented are cells within the live lymphocyte population. Statistical significance (P<0.05) is indicated by an asterisk prophylactically with anti-IL-7Rα neutralizing mAb mitigates EAE severity via partial depletion of naïve and effector memory CD4 and CD8 T cell subsets (Ashbaugh et al 2013;Lee et al 2011;Walline et al 2011). Although deficiencies in IL-7R alter both Th1 and Th17 populations, work by Lee et al strongly supports the notion that IL-7 plays a role in the development of pathogenic Th1 cells, but not the Th17 cell (Lee et al 2011).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Represented are cells within the live lymphocyte population. Statistical significance (P<0.05) is indicated by an asterisk prophylactically with anti-IL-7Rα neutralizing mAb mitigates EAE severity via partial depletion of naïve and effector memory CD4 and CD8 T cell subsets (Ashbaugh et al 2013;Lee et al 2011;Walline et al 2011). Although deficiencies in IL-7R alter both Th1 and Th17 populations, work by Lee et al strongly supports the notion that IL-7 plays a role in the development of pathogenic Th1 cells, but not the Th17 cell (Lee et al 2011).…”
Section: Discussionmentioning
confidence: 79%
“…The IL-7 signaling pathway has raised much interest as target of immunotherapy in human autoimmune disease. Recent findings showed that blockade or deletion of the IL-7 receptor ameliorates T-cell-mediated autoimmune disease, such as in C57BL/6 and SJL/J mice models of experimental autoimmune encephalomyelitis (EAE); the animal model for MS (Ashbaugh et al 2013;Lee et al 2011;Walline et al 2011).…”
mentioning
confidence: 99%
“…40 In addition, IL-7 has been shown to expand antigen-specific IL-17-producing T cells in a murine experimental autoimmune encephalomyelitis model. 41 We show in the current report detection of increased IL-17 production in rBCG-vaccinated NHPs when compared with BCG-vaccinated or control animals. IL-17 has been shown to confer protection against Mtb in murine model.…”
Section: Il-mentioning
confidence: 72%
“…This close relationship between Th1 and Th17 cells is also marked in their capacity to cause T-cell-mediated inflammation and autoimmune disease. In fact, Th17 cells have been found to have a pathogenic role in several autoimmune disorders, including experimental autoimmune encephalomyelitis [8], rheumatoid arthritis [9,10], inflammatory bowel disease [11], systemic sclerosis [12] and systemic lupus erythematosus (SLE) [13,14], which were previously thought to be mainly caused by Th1 responses. Interestingly, new studies show Th17 cells as more potent than Th1 cells in inducing disease [15], linking the cytokine IL-17 in coordinating tissue inflammation via the up-regulation of additional proinflammatory and neutrophil-recruiting cytokines and chemokines, suggesting a pro-inflammatory role in these conditions.…”
Section: Introductionmentioning
confidence: 99%